How to Write a Book Review: A Template for Writing Book Reviews and Discussion Guides - Davis, Sarah S. (New York Broke by Productions, 2020)
How to Write a Book Review is a practical how-to on writing book reviews from the #1 bestselling author of A Reader$1 (Bs Library of Book Quotes and The Great Literature Trivia Quiz Book. This detailed workbook is designed to help you grow into a confident book reviewer, whether you are writing a review for school, on your blog, or anywhere else. How to Write a Book Review will help you master a book review template that is endlessly customizable for fiction or nonfiction.s
Keywords: Writing Guides